Polymer electrolyte with low interface impedance and preparation method and application thereof
By using polymer matrix with high dielectric constant in sodium solid-state batteries to match disodium salts and small-molecular plasticizers, combining sodium tetrafluoroborate and propylene carbonate, the low conductivity and interface impedance of sodium solid-state battery electrolyte is solved by using polymer matrix with high dielectric constant in sodium solid-state batteries. The problem has significantly improved the cycle stability and safety of the battery.
Patent Information
- Application Number
- CN202411319758.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing sodium solid-state battery polymer electrolytes have problems with low room temperature ion conductivity and high interface impedance, resulting in insufficient battery cycle stability and safety.
The polymer matrix with high dielectric constant is matched with disodium salt and small molecule plasticizer, combined with sodium tetrafluoroborate and propylene carbonate, and prepared electrolyte membrane by solution casting to form a stable SEI film, reducing interface impedance and Improve conductivity.
It significantly improves the room temperature ionic conductivity and cycling stability of sodium solid state batteries, with a capacity retention rate of up to 94.4%, and enhances the structural safety of the battery.
Smart Images

Figure CN119208721A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polymer electrolyte, in particular to a polymer electrolyte with low interface impedance and a preparation method and application thereof, belonging to the technical field of sodium solid-state battery electrolytes. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries have the advantages of low cost and abundant resources, and are a strong competitor for future battery technology. In addition, sodium metal has a high theoretical specific capacity (1166mAh / g) and a low electrochemical potential (-2.71V), which makes sodium metal batteries (NMBs) have a high theoretical energy density of 275Wh / kg. However, the organic electrolytes used in traditional sodium-ion batteries have safety issues such as flammability, explosion, and dendrite penetration, which seriously hinder the further development of sodium-ion batteries. Solid electrolytes have the advantages of excellent thermal stability, mechanical properties and high energy density, and have received widespread attention. They can be mainly divided into inorganic solid electrolytes, solid polymer electrolytes and organic-inorganic composite electrolytes. Although inorganic solid electrolytes have high ionic conductivity, their poor interface stability and interface contact rigidity limit their development. In contrast, solid polymer electrolytes have the characteristics of light weight, excellent processing performance and good interface contact, and have gradually become a research hotspot.
[0003] At present, the reported sodium ion polymer matrices include polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polytrimethylene carbonate (PTMC), etc. However, the room temperature ionic conductivity of the existing sodium solid-state battery polymer electrolyte is usually around 10 - 5 S cm -1 Up to 10 -7 S cm -1 This is mainly because the polymer matrix exhibits a high degree of crystallinity at room temperature. The presence of the crystalline region will hinder the movement of the molecular chain, resulting in difficulty in ion transport. In order to effectively improve the room temperature ionic conductivity of polymer electrolytes, the commonly used strategy is to select highly dissociated salts, add inorganic fillers, plasticizers, and ionic liquids.
[0004] For example, the patent with application number 202210823149.4 discloses a method for improving the ionic conductivity of a solid electrolyte of a sodium ion battery and a polymer solid electrolyte prepared therefrom, which improves the conductive properties of the polymer by adding a highly dissociated sodium salt and adjusting the ratio of the polymer matrix and the sodium salt.
[0005] In addition, building a stable electrode-electrolyte interface is also the key to improving the electrochemical performance of the battery. Many researchers form a thin and dense solid electrolyte interface layer (SEI) at the interface between the electrolyte and the electrode by adding film-forming additives. This SEI film can effectively and evenly deposit ions and inhibit the occurrence of side reactions, thereby improving the cycle life and safety of the battery. However, the polymer electrolytes in the prior art solutions often have problems of low ion conductivity and poor cycle stability. Commonly used sodium battery film-forming additives include FEC, VC, DTD, NaDFOB and NaBF4, among which film-forming sodium salts can simultaneously increase the salt concentration of the electrolyte and form a stable SEI / CEI film, which is a better choice for developing low-impedance interfaces. Therefore, in order to improve the overall performance of the battery, it is particularly important to select suitable salts and additives to increase the room temperature ionic conductivity of the electrolyte and optimize the electrolyte-electrode interface.
[0006] For example, a polymer sodium ion solid electrolyte and its preparation method and application disclosed in application No. 202310457804.3 significantly improves the room temperature ionic conductivity and electrochemical properties of the sodium ion solid electrolyte by utilizing the synergistic effect of sodium salt and functional additives. Summary of the invention
[0007] In view of the problems existing in the prior art, the first purpose of the present invention is to provide a polymer electrolyte with low interfacial impedance. Based on the synergistic effect between the raw materials, the polymer electrolyte selects a polymer matrix with a high dielectric constant, matches it with a disodium salt and a small molecule plasticizer, and can effectively reduce the interfacial impedance and inhibit the occurrence of interfacial side reactions while improving the conductivity of the electrolyte membrane; wherein, the high dissociation degree sodium salt in the disodium salt can improve the interfacial ion mobility of the system, and then combined with sodium tetrafluoroborate, a stable SEI film is formed to prevent the interfacial side reactions of the high dissociation degree sodium salt under high pressure, and then combined with propylene carbonate to promote the solvation structure of the sodium salt, and reduce the crystallinity of the polymer, significantly improving the Na + Transport rate within the electrolyte and interfacial wettability.
[0008] The second object of the present invention is to provide a method for preparing a polymer electrolyte with low interfacial impedance. The method adopts a solution casting method. Under a protective atmosphere, raw materials including olefin polymer, sodium salt, plasticizer and solvent are mixed evenly and then cast on a mold and dried. The method is simple and easy to prepare on a large scale. At the same time, the prepared electrolyte has high room temperature ionic conductivity, and the conductivity is maintained at 10 -4 S cm -1 about.
[0009] The third object of the present invention is to provide an application of a polymer electrolyte with low interfacial impedance for preparing a sodium ion solid-state battery. The solid-state sodium battery prepared based on the polymer electrolyte provided by the present invention effectively solves the problems of severe side reactions at the interface between the electrolyte and the electrode and high interfacial impedance, and greatly improves the cycle stability and structural safety of the sodium solid-state battery. According to the test, the sodium battery provided by the present invention was cycled 650 times at a rate of 1C, and the capacity retention rate could reach up to 94.4%.
[0010] In order to achieve the above technical objectives, the present invention provides a polymer electrolyte with low interfacial impedance, characterized in that it includes the following components in mass percentage: 30-45% of olefin polymer, 10-25% of disodium salt and 35-50% of plasticizer; the disodium salt contains sodium tetrafluoroborate, the mass of which is 50-60% of the mass of the disodium salt.
[0011] The present invention significantly improves the safety, conductivity and battery cycle life of the polymer electrolyte by introducing disodium salt and organic small molecule plasticizer into the polymer electrolyte system; utilizes the synergistic effect of the double salt to significantly improve the room temperature ionic conductivity and electrochemical window of the electrolyte membrane; in addition, the introduction of the film-forming sodium salt enables the formation of a more stable SEI film at the sodium metal negative electrode interface, inhibits the occurrence of interfacial side reactions, and improves the interfacial contact; the organic small molecule plasticizer can promote the solvation structure of the salt and reduce the crystallinity of the polymer, thereby improving the fast charging performance of the battery.
[0012] It should be noted that in the technical solution provided by the present invention, each raw material component needs to be strictly implemented in accordance with the above requirements. If the amount of sodium tetrafluoroborate added in the disodium salt system is too high, the ionic conductivity of the electrolyte will decrease and the battery performance will decrease. If the amount of sodium tetrafluoroborate added is too low, the occurrence of interfacial side reactions cannot be effectively suppressed, which will lead to an increase in interfacial impedance and reduce the cycle life of the battery.
[0013] As a preferred embodiment, the olefin polymer is at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-trifluoroethylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) copolymer.
[0014] As a preferred solution, the disodium salt is sodium tetrafluoroborate and the disodium salt is sodium (trifluoromethylsulfonyl)imide, and the mass ratio of the two is 1:0.9-1.1.
[0015] As a preferred solution, the plasticizer is propylene carbonate.
[0016] As a preferred solution, the volume mass percentage of propylene carbonate to olefin polymer is 0.8-1.2 ml / g. Further preferably, the volume mass ratio of propylene carbonate to olefin polymer is 1 ml / g. Propylene carbonate can effectively promote the sodium salt solvation structure and reduce the polymer crystallization area. If too much PC is added, it will cause serious interfacial side reactions and cause the battery to fail quickly; if too little small molecule plasticizer is added, it will lead to poor processing performance of the electrolyte, curling and deformation, and cannot meet the mechanical and mechanical properties required by sodium-ion solid-state batteries.
[0017] The present invention also provides a method for preparing a polymer electrolyte with low interfacial impedance. In a protective atmosphere, raw materials including olefin polymer, disodium salt and plasticizer are uniformly mixed and then poured on a mold and dried to obtain the polymer electrolyte.
[0018] As a preferred solution, the protective atmosphere is nitrogen and / or argon.
[0019] As a preferred solution, the raw material further includes a solvent, and the volume mass ratio of the solvent to the olefinic polymer is 7 to 12 ml / g.
[0020] As a preferred solution, the solvent is acetone and / or N-methylpyrrolidone.
[0021] As a preferred solution, the raw materials are mixed by stirring, and the conditions are: temperature of 40-60°C, stirring rate of 600-1000r / min, and time of 16-24h. The stirring process involves the mixing of raw materials. If the temperature is too low, the polymer will not be completely dissolved, and the electrolyte membrane will be uneven; if the temperature is too high, the polymer may fail by depolymerization, fracture, and loss of side groups.
[0022] As a preferred solution, the drying method is at least one of protective gas drying, vacuum drying and freeze drying.
[0023] As a preferred solution, the protective gas drying condition is: drying under protective atmosphere at room temperature for 5 to 7 hours.
[0024] As a preferred solution, the protective atmosphere is nitrogen and / or argon.
[0025] As a preferred solution, the drying process is to completely evaporate the solvent in the raw material.
[0026] As a preferred solution, the thickness of the polymer electrolyte is 500-650 μm.
[0027] The present invention also provides an application of a polymer electrolyte with low interfacial impedance for preparing a sodium ion solid-state battery.
[0028] As a preferred solution, the specific preparation process of the sodium solid-state battery is as follows: the positive electrode material, the conductive agent and the binder in a mass ratio of 8:1:1 are mixed evenly and then coated on the aluminum current collector, placed in a vacuum oven at a temperature of 80°C and dried for 12 hours, taken out, and cut with a cutter with a diameter of 12 mm to obtain a positive electrode sheet; similarly, the negative electrode material, the conductive agent and the binder in a mass ratio of 8:1:1 are mixed evenly and then coated on the copper current collector, placed in a vacuum oven at a temperature of 80°C and dried for 12 hours, taken out, and cut with a cutter with a diameter of 12 mm to obtain a negative electrode sheet; the obtained positive electrode sheet is packaged with the negative electrode to obtain.
[0029] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are:
[0030] 1) The polymer electrolyte provided by the present invention is based on the synergistic effect between the raw materials. By selecting a polymer matrix with a high dielectric constant, matching it with a disodium salt and a small molecule plasticizer, the conductivity of the electrolyte membrane can be improved while the interface impedance can be effectively reduced and the occurrence of interface side reactions can be inhibited. Among them, the high dissociation degree sodium salt in the disodium salt can improve the interface ion mobility of the system, and combined with sodium tetrafluoroborate, a stable SEI film is formed to prevent the interface side reactions of the high dissociation degree sodium salt under high pressure. In addition, combined with propylene carbonate, the solvation structure of the sodium salt is promoted, and the crystallinity of the polymer is reduced, which significantly improves the Na + Transport rate within the electrolyte and interfacial wettability.
[0031] 2) In the preparation method provided by the present invention, a solution casting method is used. In a protective atmosphere, raw materials including olefin polymer, sodium salt, plasticizer and solvent are mixed evenly and then cast on a mold and dried. The method is simple and easy to prepare on a large scale. At the same time, the prepared electrolyte has high room temperature ionic conductivity, and the conductivity is maintained at 10 -4 S cm -1 about.
[0032] 3) In the technical solution provided by the present invention, the solid-state sodium battery prepared based on the polymer electrolyte provided by the present invention effectively solves the problem of serious side reactions between the electrolyte and the electrode interface and high interface impedance, and greatly improves the cycle stability and structural safety of the sodium solid-state battery. According to the test, the sodium battery provided by the present invention was cycled 650 times at a rate of 1C, and the capacity retention rate can reach up to 94.4%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The physical picture of the electrolyte membrane and the sodium negative electrode interface of the sodium solid-state battery in Comparative Examples 1-2 and Example 1 after being cycled 30 times at a rate of 1C;
[0034] Figure 2 is the thickness of the polymer electrolyte prepared in Example 1, the film thickness is 594 μm;
[0035] Figure 3 is a SEM image of the polymer electrolyte prepared in Example 1;
[0036] Figure 4 The linear voltammetry test curves and electrochemical window data of the polymer electrolytes prepared in Comparative Examples 1 to 2 and Example 1;
[0037] Figure 5 The electrochemical impedance spectra and room temperature ionic conductivity data of the polymer electrolytes prepared in Comparative Examples 1 to 2 and Example 1;
[0038] Figure 6 This is a physical picture of the polymer electrolyte prepared in Comparative Example 3;
[0039] Figure 7 The graph is a graph showing the cycle number, discharge specific capacity, and charge and discharge efficiency of the sodium solid-state battery in Comparative Examples 1 to 2 and Example 1 at a rate of 1C. DETAILED DESCRIPTION
[0040] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described in detail with reference to the accompanying drawings. It should be noted that the present invention is not limited to the following embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in the field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which belong to the protection of the present invention.
[0041] Example 1
[0042] This embodiment provides a polymer electrolyte with low interfacial impedance and a sodium solid-state battery thereof, and the steps are as follows:
[0043] Step 1. Weigh the raw materials according to the following formula: 1g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP); 0.2g of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI); 0.2g of sodium tetrafluoroborate (NaBF4); 1ml of propylene carbonate (PC); 10ml of acetone (AC). In an atmosphere-protected environment, place the above materials in a serum bottle and stir for 16 hours at a temperature of 50°C and a speed of 600r / min; apply the obtained electrolyte slurry on a glass plate and dry it in a glove box at room temperature for 5h to remove the organic solvent to obtain a self-supporting polymer electrolyte;
[0044] Step 2: Based on the obtained polymer electrolyte, a stainless steel / polymer electrolyte / stainless steel symmetrical battery is assembled, and an electrochemical workstation is used to perform an AC impedance spectroscopy test and a linear sweep voltammetry test; the room temperature ionic conductivity and electrochemical window data of the polymer electrolyte are calculated and the results are shown in Table 1;
[0045] Step 3: Based on the obtained polymer electrolyte, NVP@C is used as the positive electrode and sodium metal is used as the negative electrode to assemble the NVP@C|Na full battery, and perform cycle performance test and interface impedance test. The specific operation is: within the electrochemical window range of 2.0-3.8V, a charge and discharge cycle test is performed at room temperature with a rate of 1C to test the cycle performance of the above battery, and the number of cycles with a capacity retention rate of 80% is counted; in addition, the battery that has been cycled 30 times at this rate is tested by an electrochemical workstation for AC impedance spectroscopy, and the interface impedance data is counted. The data results of this embodiment are recorded in Table 1.
[0046] Example 2
[0047] Compared with Example 1, the negative electrode in Example 2 adopts hard carbon material; the other conditions and test types are the same as those in Example 1.
[0048] Example 3
[0049] Compared with Example 1, the negative electrode in Example 3 adopts no negative electrode (aluminum current collector); the other conditions and test types are the same as those in Example 1.
[0050] Example 4
[0051] Compared with Example 1, the positive electrode in Example 4 adopts layered oxide; the other conditions and test types are the same as those in Example 1.
[0052] Example 5
[0053] Compared with Example 1, Prussian blue is used as the positive electrode in Example 5; the other conditions and test types are the same as those in Example 1.
[0054] Comparative Example 1
[0055] Compared with Example 1, in Comparative Example 1, the double salt was changed to contain only 0.4 g of the monosalt sodium bis(trifluoromethylsulfonyl)imide (NaTFSI); the other conditions and test types were the same as those in Example 1.
[0056] Comparative Example 2
[0057] Compared with Example 1, in Comparative Example 2, the double salt is changed to contain only 0.4 g of the monosalt sodium tetrafluoroborate (NaBF4); the other conditions and test types are the same as those in Example 1.
[0058] Comparative Example 3
[0059] Compared with Example 1, in Comparative Example 3, 0.3 g of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) and 0.1 g of sodium tetrafluoroborate (NaBF4) were used; and the remaining conditions and test types were the same as those in Example 1.
[0060] Comparative Example 4
[0061] Compared with Example 1, in Comparative Example 4, 0.1 g of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) and 0.3 g of sodium tetrafluoroborate (NaBF4) were used; and the remaining conditions and test types were the same as those in Example 1.
[0062] Comparative Example 5
[0063] Compared with Example 1, Comparative Example 5 does not contain PC, and the other conditions and test types are the same as those of Example 1. However, in Comparative Example 5, during the evaporation of the solvent, the polymer electrolyte film slowly curled and gradually hardened, and the battery could not be assembled.
[0064] Comparative Example 6
[0065] Compared with Example 1, the PC content in Comparative Example 6 is 0.5 ml, and the other conditions and test types are the same as those in Example 1. However, in Comparative Example 6, during the evaporation of the solvent, the polymer electrolyte film slowly curled and gradually hardened, and the battery could not be assembled.
[0066] Comparative Example 7
[0067] Compared with Example 1, the PC content in Comparative Example 7 is 0.8 ml; the other conditions and test types are the same as those in Example 1.
[0068] Comparative Example 8
[0069] Compared with Example 1, the PC content in Comparative Example 8 is 1.5 ml; the other conditions and test types are the same as those in Example 1.
[0070] Comparative Example 9
[0071] Compared with Example 1, the PC content in Comparative Example 9 is 2 ml; the other conditions and test types are the same as those in Example 1.
[0072] Comparative Example 10
[0073] Compared with Comparative Example 1, the negative electrode in Comparative Example 10 adopts hard carbon material; the other conditions and test types are the same as those in Example 1.
[0074] Comparative Example 11
[0075] Compared with Comparative Example 1, the negative electrode in Comparative Example 11 adopts no negative electrode (aluminum current collector); the other conditions and test types are the same as those in Example 1.
[0076] Comparative Example 12
[0077] Compared with Comparative Example 1, the positive electrode in Comparative Example 12 adopts layered oxide; the other conditions and test types are the same as those of Comparative Example 1.
[0078] Comparative Example 13
[0079] Compared with Comparative Example 1, Prussian blue is used as the positive electrode in Comparative Example 13; the other conditions and test types are the same as those of Comparative Example 1.
[0080] Table 1
[0081]
[0082]
[0083] It can be seen from the data of Example 1 and Comparative Examples 3 and 4 in Table 1 that as the proportion of sodium tetrafluoroborate increases, the cycle life and interface impedance first increase and then decrease, and the performance of the electrolyte obtained is best when the proportion of sodium tetrafluoroborate is 50% of the mass of the disodium salt; further, it can be seen from Comparative Examples 6 to 9 that under the premise that the proportion of sodium tetrafluoroborate is 50% of the mass of the disodium salt, as the proportion of PC increases, the ionic conductivity is significantly improved, the interface impedance gradually decreases, and the cycle stability is also improved. When the mass volume ratio of PC to the polymer matrix is 1ml / g, the solid-state battery has the best performance, but further increasing the PC content will cause the cycle performance improvement effect of the battery to show a downward trend. Therefore, the proportion of sodium tetrafluoroborate in the disodium salt and the proportion of propylene carbonate must be within the scope required by the present invention to achieve the corresponding technical purpose.
[0084] In Example 1 provided by the present invention, the synergistic effect of the two sodium salts improves the cycle stability to 650 cycles, and the capacity retention rate is as high as 94.4%, and its cycle life is three times that of the case without adding sodium tetrafluoroborate. Figure 5 It can also be seen that the introduction of sodium tetrafluoroborate can significantly improve the electrochemical window of the polymer electrolyte membrane. Figure 4 It can be seen that the ionic conductivity of the double salt still remains at 10 -4 S cm -1 In order to prove the interface stability, the present invention also disassembled the batteries after cycles in Comparative Example 1, Comparative Example 2 and Example 1, and the results are as follows: Figure 1As shown, the electrolyte membrane in Comparative Example 1 turns black, indicating that serious side reactions occur at the interface. In comparison, the electrolyte membranes in Example 1 and Comparative Example 2 do not have serious discoloration, indicating that no serious side reactions occur at the interface. However, in Comparative Example 2, NaBF4 alone is used as the sodium salt, and its cycle stability is only 3 weeks, and stable charge and discharge cannot be performed. In summary, only by using a disodium salt system containing sodium tetrafluoroborate can the occurrence of interfacial side reactions be significantly inhibited while improving the electrolyte cycle stability, thereby stabilizing the battery interface.
Claims
1. A polymer electrolyte with low interfacial impedance, characterized in that: The invention comprises the following components in percentage by weight: 30-45% of olefin polymer, 10-25% of disodium salt and 35-50% of plasticizer; the disodium salt contains sodium tetrafluoroborate, the weight of which is 50-60% of the weight of the disodium salt.
2. A polymer electrolyte with low interfacial impedance according to claim 1, characterized in that: The olefin polymer is at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-trifluoroethylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) copolymer.
3. A polymer electrolyte with low interfacial impedance according to claim 1, characterized in that: The disodium salt is sodium tetrafluoroborate and the disodium salt is sodium (trifluoromethylsulfonyl)imide, and the mass ratio of the two is 1:0.9-1.
1.
4. A polymer electrolyte with low interfacial impedance according to claim 1, characterized in that: The plasticizer is propylene carbonate.
5. The method for preparing a polymer electrolyte with low interfacial impedance according to any one of claims 1 to 4, characterized in that: Under a protective atmosphere, raw materials including olefin polymer, disodium salt and plasticizer are mixed evenly and poured on a mold, and then dried to obtain the product.
6. The method for preparing a polymer electrolyte with low interfacial impedance according to claim 5, characterized in that: The protective atmosphere is nitrogen and / or argon; the raw material also includes a solvent, and the volume mass ratio of the solvent to the olefin polymer is 7-12 ml / g; the solvent is acetone and / or N-methylpyrrolidone.
7. The method for preparing a polymer electrolyte with low interfacial impedance according to claim 5, characterized in that: The raw materials are mixed by stirring, and the conditions are: temperature of 40-60° C., stirring rate of 600-1000 r / min, and time of 16-24 h.
8. The method for preparing a polymer electrolyte with low interfacial impedance according to claim 5, characterized in that: The drying method is at least one of protective gas drying, vacuum drying and freeze drying; the protective gas drying conditions are: drying for 5 to 7 hours under room temperature in a protective atmosphere; the protective atmosphere is nitrogen and / or argon.
9. The method for preparing a polymer electrolyte with low interfacial impedance according to claim 6, characterized in that: The drying process is to completely evaporate the solvent in the raw material; the thickness of the polymer electrolyte is 500-650 μm.
10. The use of a polymer electrolyte with low interfacial impedance according to any one of claims 1 to 4, characterized in that: Used to prepare sodium-ion solid-state batteries.
Citation Information
Patent Citations
Polymer sodium ion solid electrolyte as well as preparation method and application thereof
CN116315074A
Organogel polymer electrolytic solution, preparation method, application, sodium-based dual-ion battery and preparation method thereof
CN109638344A
Method for improving ionic conductivity of solid electrolyte of sodium-ion battery and polymer solid electrolyte prepared by method
CN115101810A
Sodium battery composite solid electrolyte and preparation method and application thereof
CN115642305A
Preparation method of quasi-solid-state sodium ion electrolyte with wide temperature range and quasi-solid-state sodium battery
CN118213615A
Cited By
Polymer electrolyte and preparation method and application thereof
CN120824418A
